Limonoids from the fruits of Chisocheton lasiocarpus (Meliaceae). Issue 1 (2nd January 2023) - Katja, Dewa Gede; Hilmayanti, Erina; , Nurlelasari; Mayanti, Tri; Harneti, Desi; Maharani, Rani; Farabi, Kindi; , Darwati; Lesmana, Ronny; Fajriah, Sofa; Supratman, Unang; Azmi, Mohamad Nurul; et al.
Abstract: Two new azadirone-type limonoids, namely lasiocarpine A (1 ) and lasiocarpine B (2 ) were isolated from the fruit of Chisocheton lasiocarpus along with three known limonoids (3 –5 ). UV, IR, one- and two- dimensional NMR, and mass spectrometry were used to determine the chemical structure of the isolated compounds. Furthermore, their cytotoxic activity against breast cancer cell line MCF-7 was evaluated using PrestoBlue reagent. From these compounds, lasiocarpine A (1 ) showed the strongest activity with an IC50 value of 43.38 μM. Graphical Abstract: UF0001